2021
DOI: 10.1007/s12639-021-01436-4
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of Cryptosporidium species in humans from southern Africa (2000–2020)

Abstract: The epidemiology of cryptosporidiosis in southern Africa is largely unknown. The disease is associated with diarrhea and nutritional deficiencies, leading to severe morbidity and mortality among immune-compromised patients. This study aimed to assess the pooled prevalence of Cryptosporidium spp. infection among immune-compromised humans in southern Africa over the past 20 years. Reports of Cryptosporidium spp. infection in humans published between 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Only Cryptosporidium (13%) and Giardia lamblia (8%) parasites were detected in the stool samples. According to Omoladi et al [ 79 ], the overall prevalence of Cryptosporidium spp infection in Southern African countries was 16.8%, which is mainly due to the high number of immunocompromised individuals in the region suffering from HIV/Aids. In this study, no samples tested positive for Entamoema histolytica or Cyclospora cayetanensis.…”
Section: Discussionmentioning
confidence: 99%
“…Only Cryptosporidium (13%) and Giardia lamblia (8%) parasites were detected in the stool samples. According to Omoladi et al [ 79 ], the overall prevalence of Cryptosporidium spp infection in Southern African countries was 16.8%, which is mainly due to the high number of immunocompromised individuals in the region suffering from HIV/Aids. In this study, no samples tested positive for Entamoema histolytica or Cyclospora cayetanensis.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental transmission studies have also confirmed its infectivity for calves, pigs, rabbits, rats and mice and humans [ 173 , 174 ]. It is the third most common Cryptosporidium species in humans [ 1 , 175 ] and has also been identified in colon adenocarcinoma tissue in an immunocompetent Polish patient [ 176 ]. Phylogenetic analysis suggests that C. meleagridis may originally have been a mammalian parasite that secondarily became established in birds [ 177 ].…”
Section: Zoonotic Cryptosporidium Species and Genotypesmentioning
confidence: 99%
“…A direct microscopic method is obtained using morphological identification with a 100× oil immersion lens. It uses different staining techniques such as hot or cold modified Ziehl-Neelsen (MZN) and auramine phenol to detect the oocyst containing four mature sporozoites (7). The microscopical method is an excellent tool and highly economical but requires expertise and experienced diagnostic personnel to reduce false-positive results and thus can be time-consuming and also parasites species and multiple infections the microscopic examination cannot detected these issues (8,9).…”
Section: Introductionmentioning
confidence: 99%